The construction sector in Galicia: Corporate social responsibility and financial results - Vilar Fernández, Juan Manuel; Fe Marqués, Jaime; Vasallo Rapela, Alejandro M. (Revista Galega de Economía, 2019)
The company’s social responsibility, also called corporate social responsibility (CSR), is considered a key strategic factor in management. The purpose of this paper is to analyze the existing relationships between the CSR principles and the profitability of companies in the construction sector in Galicia. To this end, a review of the concept of CSR and its evolution is made; then, an analysis of the relationship between CSR and business results for Galician companies of the construction sector is carried out; finally, quantitative indicators are developed to evaluate the management and performance of the company and the theoretical approaches are compared with the results obtained through econometric modeling for a sample of 100 companies. This comparative analysis is done through return on assets (ROA,) or economic profitability, and return on equity (ROE), or financial profitability. We conclude that there is a positive relationship between financial returns and CSR, so the latter is consolidated as a source of competitive advantage.